Telomere maintenance in liquid crystalline chromosomes of dinoflagellates - Fojtová, Miloslava; Wong, Joseph T Y; Dvorácková, Martina; Yan, Kosmo T H; Sýkorová, Eva; Fajkus, Jirí (Chromosoma, 2010)
The organisation of dinoflagellate chromosomes is exceptional among eukaryotes. Their genomes are the largest in the Eukarya domain, chromosomes lack histones and may exist in liquid crystalline state. Therefore, the study of the structural and functional properties of dinoflagellate chromosomes is of high interest. In this work, we have analysed the telomeres and telomerase in two Dinoflagellata species, Karenia papilionacea and Crypthecodinium cohnii. Active telomerase, synthesising exclusively Arabidopsis-type telomere sequences, was detected in cell extracts. The terminal position of TTTAGGG repeats was determined by in situ hybridisation and BAL31 digestion methods and provides evidence for the linear characteristic of dinoflagellate chromosomes. The length of telomeric tracts, 25-80 kb, is the largest among unicellular eukaryotic organisms to date. Both the presence of long arrays of perfect telomeric repeats at the ends of dinoflagellate chromosomes and the existence of active telomerase as the primary tool for their high-fidelity maintenance demonstrate the general importance of these structures throughout eukaryotes. We conclude that whilst chromosomes of dinoflagellates are unique in many aspects of their structure and composition, their telomere maintenance follows the most common scenario.
Keywords: Dinoflagellida; Chromatin; telomery; repetitivní sekvence nukleových kyselin; Chromosomes; replikace DNA; DNA Breaks; telomerasa; protozoální DNA; zlomy DNA; Repetitive Sequences, Nucleic Acid; Telomerase; chromozomy; kapalné krystaly; DNA Replication; chromatin; Dinoflagellata; DNA, Protozoan; Telomere; Liquid Crystals